Screening of osmotic stress-tolerant bacteria for plant growth promotion in wheat (Triticum aestivum L.) and brinjal (Solanum melongena L.) under drought conditions - Patel, P.; Patil, T.; Maiti, S.; Paul, D.; Amaresan, N. (Letters in Applied Microbiology, 2022)
Drought stress adversely affects plant growth and productivity. Therefore, the application of plant growth-promoting bacteria is a viable option for combating drought resistance in crops. In this study, 144 bacteria were isolated from the Kutch desert soil in Gujarat. Based on osmotic stress tolerance and PGP properties, two strains, Bacillus tequilensis (KS5B) and Pseudomonas stutzeri (KS5C) were tested for their effect on wheat (Triticum aestivum L.) and brinjal (Solanum melongena L.) under drought stress conditions. Inoculation with osmotic stress-tolerant bacteria showed 15 center dot 15-29 center dot 27% enhancement in root length of wheat and 15 center dot 27-32 center dot 59% in brinjal plants. Similarly, the enhancement of shoot length ranged from 14 center dot 72 to 37 center dot 70% for wheat and 59 center dot 39-95 center dot 94% for brinjal plants. Furthermore, the inoculated plants showed significant improvement in chlorophyll content and antioxidant properties such as proline, peroxidase and polyphenol oxidase activity compared to the control. Therefore, the bacterial strains identified in this study can be used to mitigate drought stress and enhance plant biomass.
Keywords: Antioxidant; brinjal; drought; plant growth; Wheat